Proceedings of the 2017 International Conference on Organizational Innovation (ICOI 2017) 2017
DOI: 10.2991/icoi-17.2017.32
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trust, Satisfaction, and Commitment on Customer Loyalty At the Alfamart Retail in Surabaya, East Java - Indonesia

Abstract: The research objective has to determine the Effect of Trust, Satisfaction and Commitment on Customer Loyalty in the Alfamart Retail at Surabaya, East Java, Indonesia. Hopefully will be able to the AEC 2015 retail business in Indonesia's is expected to be better.Modern retail is essentially a development of traditional retail. This retail formats emerge and evolve as economic development, technology, and lifestyle that makes people demand more convenience in shopping. The population used all of Alfamart retail … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The results of this study are aligned with the outcomes of a previous research conducted to investigate the impact of Satisfaction on Customer Loyalty which explained that Satisfaction have a significant impact on the Customer loyalty which implies that Satisfaction is considered to be an important element to drive customer loyalty, More the customer is satisfied the more it is successful to fit its image in consumer's mind which will ultimately boost customer loyalty. (Sutanto & Djati, 2017) also provides support for the results of present hypothesis which affirmed that customer satisfaction has a significant impact on customer loyalty.…”
Section: Satisfactionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results of this study are aligned with the outcomes of a previous research conducted to investigate the impact of Satisfaction on Customer Loyalty which explained that Satisfaction have a significant impact on the Customer loyalty which implies that Satisfaction is considered to be an important element to drive customer loyalty, More the customer is satisfied the more it is successful to fit its image in consumer's mind which will ultimately boost customer loyalty. (Sutanto & Djati, 2017) also provides support for the results of present hypothesis which affirmed that customer satisfaction has a significant impact on customer loyalty.…”
Section: Satisfactionsupporting
confidence: 84%
“…The outcomes of this study demonstrated that trust significantly impacts customer loyalty. Moreover the rest two variables were also found to have a significant impact on customer loyalty (Sutanto & Djati, 2017).…”
Section: Trust and Customer Loyaltymentioning
confidence: 92%
“…There is an influence of commitment on service quality. (Alsharari et al, 2017); (Esmaeilpour & Ranjbar, 2018); (Hadiwijaya & Febrianty, 2019); (Hidayat et al, 2015); (Kungumapriya & Malarmathi, 2018); (Pahi et al, 2017); (Sari et al, 2018); (Setiawan et al, 2020); (Singh, 2016); (Sutanto, 2019). 4…”
Section: Introductionmentioning
confidence: 99%